2003
DOI: 10.1128/aem.69.10.6018-6024.2003
|View full text |Cite
|
Sign up to set email alerts
|

Axial Dynamics, Stability, and Interspecies Similarity of Bacterial Community Structure in the Highly Compartmentalized Gut of Soil-Feeding Termites ( Cubitermes spp.)

Abstract: The highly compartmentalized gut of soil-feeding termites is characterized by pronounced axial dynamics in physicochemical conditions and microbial processes. The hindgut of soil-feeding termites is highly compartmentalized and characterized by pronounced axial dynamics of oxygen, intestinal pH, and redox potential (1,3,4,14) and of microbial processes such as hydrogen production, methanogenesis, and reductive acetogenesis (26,29). Recent studies have provided strong evidence for an important role of the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
63
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 29 publications
9
63
0
Order By: Relevance
“…Like that of the bovine rumen, the termite gut microbial community has garnered attention due to its enzymatic profile (35,308). These communities contain archaea, fungi, protists, and dozens to hundreds of bacterial taxa, several of which are unique to the termite gut, and likely contain more novel species (31,137,138,185,242,297,298,369). Bacterial members of these communities affiliate with more than 15 phyla, including the Spirochaetes, Fibrobacteres, Proteobacteria, CFB, Firmicutes, and Actinobacteria (137,242,297,298,369).…”
Section: Other Host-associated Communitiesmentioning
confidence: 99%
“…Like that of the bovine rumen, the termite gut microbial community has garnered attention due to its enzymatic profile (35,308). These communities contain archaea, fungi, protists, and dozens to hundreds of bacterial taxa, several of which are unique to the termite gut, and likely contain more novel species (31,137,138,185,242,297,298,369). Bacterial members of these communities affiliate with more than 15 phyla, including the Spirochaetes, Fibrobacteres, Proteobacteria, CFB, Firmicutes, and Actinobacteria (137,242,297,298,369).…”
Section: Other Host-associated Communitiesmentioning
confidence: 99%
“…[3][4][5][6][7][8] Recently, Hongoh et al 9) performed comparative analysis of the bacterial community in the gut of wood-feeding termites, Microcerotermes and Reticulitermes species, based on clonal 16S rRNA genes, and showed that the community structure is basically consistent within a termite genus, and that a majority of the clones formed monophyletic clusters with sequences from other termite species. These results support the coevolution of gut bacteria and host termites, and imply the existence of bacterial lineages indispensable to their wood-feeding life style.…”
mentioning
confidence: 99%
“…Studies using rRNA-based techniques such as rRNA gene clone sequencing, 5) terminal restriction fragment length polymorphisms (T-RFLP) analysis, 6) and fluorescence in situ hybridization (FISH) 7) have shown that the termite gut is a rich reservoir of novel and diverse microorganisms, and highly compartmentalized beyond our expectations, and have also indicated that our knowledge of the relevant ecosystem is still insufficient for comprehensive understanding of this symbiosis.…”
mentioning
confidence: 99%